2000
DOI: 10.1177/00220345000790020701
|View full text |Cite
|
Sign up to set email alerts
|

Human Gingival Crevicular Fluid Contains MRP8 (S100A8) and MRP14 (S100A9), Two Calcium-binding Proteins of the S100 Family

Abstract: Human gingival crevicular fluid contains unidentified proteins which might play a role as markers in periodontal diseases. Therefore, low-molecular-weight proteins found in human gingival crevicular fluid (GCF), but absent from serum, were identified in the present study by means of two-dimensional electrophoresis (2-D PAGE) analysis. GCF, serum, and whole saliva were collected from periodontitis and healthy subjects, as well as from edentulous and newborn subjects. Protein samples were separated by two-dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
2
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 49 publications
3
69
2
1
Order By: Relevance
“…The present data indicated that GCF calprotectin levels increased as the periodontal disease progresses from health to disease, but similar in G-AgP and CP. Our findings are consistent with the previous data showing the role of calprotectin as an inflammatory marker of periodontal disease [11,12,42,43]. Kaner et al [44] have demonstrated that GCF calprotectin levels are significantly correlated with the levels of periodontal inflammation and decreased after periodontal therapy in G-AgP patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present data indicated that GCF calprotectin levels increased as the periodontal disease progresses from health to disease, but similar in G-AgP and CP. Our findings are consistent with the previous data showing the role of calprotectin as an inflammatory marker of periodontal disease [11,12,42,43]. Kaner et al [44] have demonstrated that GCF calprotectin levels are significantly correlated with the levels of periodontal inflammation and decreased after periodontal therapy in G-AgP patients.…”
Section: Discussionsupporting
confidence: 93%
“…It has been previously shown that calprotectin was present in human dental calculus and suggested that it might be derived from gingival crevicular fluid (GCF), saliva and dental plaque [10]. Studies have shown that calprotectin level in GCF from periodontitis patients is higher than that from healthy subjects and positively correlated with clinical and biochemical markers of periodontal inflammation [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…(Farah et al, 2010a) In severe cases, the defective enamel is lost shortly after molar eruption, exposing underlying dentine favoring the tooth sensitivity and the dental carious lesion. (Kilpatrick, 2009) Lately, MIH is understood as a hypocalcified subtype of enamel defect with reduced mineral content, low residual content of amelogenins and the presence of more than 16 types of proteins in affected teeth, thirteen of which are found in saliva and crevicular fluid (Kojima et al, 2000, Denny et al, 2008 and the three others (hemoglobin, albumin, complement C3) are major components of blood. Moreover, protein composition of MIH enamel varies with severity of enamel defect.…”
Section: Definitionmentioning
confidence: 99%
“…They are also expressed at very high levels in the synovial fluid and plasma of patients suffering from rheumatoid arthritis and gout (C. Ryckman and P. A. Tessier, unpublished observations). Local secretion of the proteins has also been detected in periodontal infections and in experimental murine abscesses (14,15). Recent results obtained in our laboratory demonstrate that S100A8 and S100A9 are also important for neutrophil migration in a murine model of acute gouty arthritis (C. Ryckman and P. A. Tessier, unpublished observations).…”
Section: Figurementioning
confidence: 99%